Viscous flow and collapse of macroscopic cavities in a granular material in terms of a Darcylet. (26th June 2020) - Sano, Osamu
Abstract : Viscous flow through a granular material that has a macroscopic cavity is obtained on the basis of the Stokes and the generalized Darcy's equation. A new singularity termed 'Darcylet', a fundamental flow in the granular material that acts like a point force with negative direction, is proposed, which is applied to elucidate the interaction of two cavities. Depending on the configuration of the latter, the volume flux into the cavity increases, which enhances the local stresses on the boundary, causes the collapse of cavities and triggers landslides. This article is part of the theme issue 'Stokes at 200 (Part 1)'.